Titanium dioxide nanotubes applied to conventional glass ionomer cement influence the expression of immunoinflammatory markers: An in vitro study - Rangel-Coelho, João Pedro; Gogolla, Pedro Viel; Meyer, Maria Davoli; Simão, Lucas Carvalho; Costa, Bruna Carolina [UNESP]; Casarin, Renato Côrrea Viana; Santamaria, Mauro Pedrine; Teixeira, Lucas Novaes; Peruzzo, Daiane Cristina; Lisboa-Filho, Paulo Noronha [UNESP]; Nociti-Jr, Francisco Humberto; Kantovitz, Kamila Rosamilia (Elsevier, 2024)
Objectives: To assess the impact of different concentrations TiO2-nt incorporated into a glass ionomer cement on the proliferation, mitochondrial metabolism, morphology, and pro- and anti-inflammatory cytokine production of cultured fibroblasts (NIH/3T3), whether or not stimulated by lipopolysaccharides (LPS-2 μg/mL, 24 h). Methods: TiO2-nt was added to KM (Ketac Molar EasyMix™, 3 %, 5 %, 7 % in weight); unblended KM was used as the control. The analyses included: Cell proliferation assay (n = 6; 24/48/72h); Mitochondrial metabolism assay (n = 6; 24/48/72h); Confocal laser microscopy (n = 3; 24/48/72h); Determination of biomarkers (IL-1β/IL-6/IL-10/VEGF/TNF) by using both multiplex technology (n = 6; 12/18 h) and the quantitative real-time PCR assay (q-PCR) (n = 3, 24/72/120 h). The data underwent analysis using both the Shapiro-Wilk and Levene tests, and by generalized linear models (α = 0.05). Results: It demonstrated that cell proliferation increased over time, regardless of the presence of TiO2-nt or LPS, and displayed a significant increase at 72 h; mitochondrial metabolism increased (p < 0.05), irrespective of exposure to LPS (p = 0.937); no cell morphology changes were observed; TiO2-nt reverted the impact of KM on the secreted levels of the evaluated proteins and the gene expressions in the presence of LPS (p < 0.0001). Conclusions: TiO2-nt did not adversely affect the biological behavior of fibroblastic cells cultured on GIC discs.
Keywords: Fibroblasts; Glass ionomer cements; Interleukins; Nanotechnology; Proteome; Titanium dioxide